Peningkatan Hasil Belajar pada Pembelajaran Tematik melalui Model Pembelajaran Problem Based Learning di Kelas 2 SDN Ngijo 01 Semarang - Subhiya Dwi Astuti; Nursiwi Nugraheni; Durratus Sa’diyah (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The purpose of this research was to improve the learning outcomes of class 2 students at SDN Ngijo 01 Semarang in thematic learning through the Problem Based Learning model. This type of research is classroom action research. This study consisted of 5 cycles, each cycle consisting of 4 stages, namely planning, implementation, observation and reflection. The subjects of this study were the 2nd grade students of SDN Ngijo 01 Semarang, totaling 24 students consisting of 9 female students and 15 male students. Data collection methods in this study are tests and observations. The research instruments used in this study were test questions and observation sheets. The test data on learning outcomes were analyzed descriptively quantitatively and the data in the form of observations were analyzed descriptively qualitatively. The success criteria achieved by students and teachers in this study were seen from changes towards improvement and increased student learning outcomes. The results showed that the use of the Problem Based Learning learning model was able to improve student learning outcomes in thematic learning. This can be seen from the percentage of students' scores in the pre-cycle achieving 50% classical mastery level, namely 12 out of 24 students. In cycle I 59% completeness classical, cycle II 62.5% completeness classical, cycle III 71% completeness classical, cycle IV 75% completeness classical, cycle V 87.5% completeness classical. Due to the increase in student learning outcomes from having met the target of 85% so that the cycle ends in cycle V. Students show activeness in the learning process and students also understand more because they have direct learning experiences.